Analisis Pengabulan Izin Poligami Dengan Alasan Menghamili Calon Istri Kedua (Putusan Pengadilan Agama Perkara Nomor 556/Pdt.G/2021/PA.Gorontalo - Hasan, Tia; Nusa, Aprianto; Arpin, Arpin; Aliyas, Aliyas (Unisan Law Review, 2025)
As for the results of the research (1), the judge's considerations regarding the granting of polygamy were based on juridical considerations, namely that the panel of judges granted their decision because of the applicant's acknowledgment that he was able to support his wife, act fairly, and take responsibility for his actions in causing the prospective second wife to become pregnant. Furthermore, the sociological consideration is that the judge in deciding the case regarding the application for polygamy due to pregnancy out of wedlock which has fulfilled the requirements for polygamy (2) There are three legal consequences in granting the application for a polygamy permit. Firstly, the parties referred to here are the husband, first wife and second wife who have responsibilities, rights and obligations according to the same roles. The second is that the position of children is the same as long as the child is from a valid marriage or the legal status of a child born outside of a valid marriage has been validated. And the third is regarding property, namely that the second wife cannot inherit the assets inherited from the first wife with the rules in Islamic. Judges should always be careful in deciding a case because people will think it is very easy of a request for permission for polygamy at the Religious Court is quite reasonable because of pregnancy.